Penerapan Value Engineering Untuk Menghemat Biaya Produksi Sapu Ijuk Pada UD. Maju Jaya - Muhammad Rizky Armayanda; Muhammad Fazri Pasaribu (JURUTERA - Jurnal Umum Teknik Terapan, 2017)
Maju Jaya is one of the palm fiber broom producers in Medan Senembah village, Tanjung Morawa Subdistrict, Deli Serdang District. The number of palm fiber broom producers in the Medan Senembah village with business locations that are close to each other makes business competition more competitive between palm fiber broom producers. One effort to win market competition is to reduce production costs. Value engineering method is one of the methods used to save production costs by applying to the improvement of the value, performance and costs of palm fiber broom products, which consist of durability, strength, aesthetics, cost and comfort criteria. Value engineering work plan consists of five phases, namely information phase, creative phase, analysis phase, development phase and recommendation phase. The zero-one matrix method is applied in the analysis phase to help determine the total performance and value of alternative proposals that are in accordance with the wishes of consumers. The results showed that the chosen alternative was the first alternative, that the broom sticks functioned directly as hangers and broom stems were painted with rod coloring with a performance of 39.33399, a value of 1.66 and a cost savings of Rp. 240.56, - or 2.1% each palm fiber broom unit, with the demand for palm fiber broom reaching 73,200 each year, the amount of savings obtained is Rp. 17,608,992 each year.